Orbital and periorbital migration of silicone oil associated with emphysema development after retinal detachment repair – Case report and literature review - Algethami, Ahmed; Schellini, Silvana Artioli; Elkhamary, Sahar M.; Talea, Mohammad A.; Semidey, Valmore A. (Elsevier, 2022)
Purpose: To report a very rare case of silicone oil (SO) migration and emphysema development in the orbit and periorbital tissue, including the lids and subconjunctival space, after a fourth pars plana vitrectomy (PPV) for retinal detachment (RD) treatment. Observations: A 53-year-old woman with a recurrent rhegmatogenous RD in the right eye underwent a fourth PPV under local anesthesia and 23-gauge vitrectomy with fluid-air exchange and SO injection. Localized choroidal detachment occurred during fluid–air exchange near the end of the surgery. High-pressure infusion of air was used as a temporary control measure prior to SO injection. In the early postoperative period, the patient developed hemifacial and periorbital swelling and the air trapped in the upper lid was associated with lid ptosis and conjunctival chemosis. The emphysema resolved with clinical management, and the mechanical ptosis subsided after partial SO removal from the lid. Conclusions and Importance: The SO migration and emphysema in our case were presumably related to the multiple previous sclerotomies. Periorbital emphysema can show spontaneous resolution, but the migrated SO requires surgical management.
Keywords: Air-fluid exchange; Emphysema; Orbital; Pars plana vitrectomy; Periorbital; Retinal detachment; Silicone oil